Sosiologi Sebagai the Queen of Social Sciences: Sebuah Refleksi - Susilo, Rachmad K. Dwi (Laboratorium Sosiologi, Program Studi Sosiologi, Fakultas Ilmu Sosial, Universitas Nahdlatul Ulama Indonesia (UNUSIA) Jakarta, 2020)
Sociologists are noble expertise, because sociologists are the ones who know, understand and master the niches of society both visible and invisible. Both the side of society which is located on the surface and in the deepest part are understood by sociologist. However, when we find in the field, sociology is still powerless. The task of prophecy and the caliphate that are inherent in sociologists is difficult to prove. The percentage of scientific involvement is mostly occupied by applied socio-political scientists. In fact, the age of this knowledge is quite long, Ibn Khaldun developed sociology in the 14th century, and August Comte gave the name Sociology in the 18th century. In Indonesian context, if it is calculated from Selo Soemardjan completing his studies from America in 1959, the age of sociology is 61 years old. Sociology has its jargon as the queen of the social sciences but, however, the question, is sociology really the queen? Even though Indonesian sociologist already have associations of both ISI (Indonesian Sociology Association) and APSSI (Indonesian Sociology Departement Association) that have been working quite actively, we have difficulty finding good models of sociologists in the professional field. The author realizes that the university has not succeeded in producing sociologists who can truly work without academic attributes; therefore, the purpose of this article is to understand and explain the dilemmas faced by sociology and Indonesian sociologists; then, unravel these convoluted problems and then propose steps to solve the problems. The author starts from the fundamental problems which are then linked to basic principles in sociology. Then, building a sociology house and sociological challenges. Finally, the writer proposes as a solution.